Georgia Architectural and Historic Properties Survey of 726 Jackson St., Valdosta, Ga. - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 726 Jackson St., Valdosta, Ga. December 1980. One story double pen house with additions. Tin, multi-gabled roof, screened-in porch. Shiplap siding. Interior and exterior chimney. Double hung sash windows with 6/6 lights. Set on brick piers. Fair condition. Date of Construction: App. 1900. Part of a district of other houses which are similar and are of the same age - has significance as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 726 Jackson St., Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 81.4 MB (85,456,056 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)